A divisão de tarefas no balanceamento de carga em uma linha de produção - Silva, Carlos Alexandre Xavier da (2017)
In one version of the Simple Assembly Line Balancing Problem (SALBP) tasks are assigned to stations along an assembly line with a fixed cycle time in order to minimise the required number of stations. It is assumed that the total work needed for each product unit has been partitioned into economically indivisible tasks. In practice, it may be that the minimal number of stations can be reduced when it is possible to further divide particular tasks in limited ways even with additional time penalty costs. Allowing task division leads to a new assembly line balancing problem, TDALBP (Task Division Assembly Line Balancing Problem) and a solution procedure for it. This work introduces a mathematical model for the TDALBP and presents promising computational results for the adaptation of some classical SALBP instances from the research literature. The results demonstrate that the TDALBP has the potential to significantly improve assembly line performance.